The effect of ambient particle matters on hospital admissions for cardiac arrhythmia: a multi-city case-crossover study in China - Qiwen Zheng; Hui Liu; Jun Zhang; Dafang Chen (BMC, 2018)
Abstract Background The relationship between particle matters (PMs) and cardiac arrhythmia has been investigated in numerous studies. However, evidence from developing countries is limited. The aim of this study was to evaluate the association between ambient PMs and hospital admissions for cardiac arrhythmia in China and to examine the potential effect modifiers. Methods A time-stratified case-crossover analysis was conducted in 26 large Chinese cities. In total, we identified 175,265 hospital admissions for cardiac arrhythmia between January 2014 and December 2015 from electronic hospitalization summary reports. Conditional logistic regression was performed to estimate the percentage changes in cardiac arrhythmia admissions in relation to interquartile range increases in air pollutants. Age, gender and prespecified comorbid health conditions including hypertension, diabetes, congestive heart failure and hyperlipidemia were stratified to evaluate susceptibility factors. Results PMs levels were positively associated with the number of hospital admissions for cardiac arrhythmia. Both PM2.5 and PM10 had the strongest impact on lag 2 days. An interquartile range increase in PM2.5 (47.5 μg/m3) and PM10 (76.9 μg/m3) concentrations on lag 2 days was associated with increments of 2.09% (95%CI, 1.58-2.60%) and 2.33% (95%CI, 1.68-2.97%) in hospital admission for cardiac arrhythmia, respectively. Evidence of effect modification by age and comorbid diabetes was observed. The elderly (> 65 years) and patients with comorbid diabetes were more likely to be hospitalized for cardiac arrhythmia following exposure to high levels of PMs. Conclusions This study found an increased risk of arrhythmia admissions associated with PM2.5 and PM10 levels among 26 Chinese cities. The associations of PMs with arrhythmia admissions were stronger in aged population and people with diabetes.